Suprascapular nerve block for the treatment of adhesive capsulitis: a randomised double-blind placebo-controlled trial. Issue 2 (23rd November 2022) - Shanahan, E Michael; Gill, Tiffany K; Briggs, Elizabeth; Hill, Catherine L; Bain, Gregory; Morris, Timothy
Abstract : Objective: Adhesive capsulitis is a common painful shoulder condition. Treatment for the condition remains unsatisfactory. Suprascapular nerve block (SSNB) shows promise as a treatment option for adhesive capsulitis but there are no randomised controlled trials that examine its effect on pain or duration of the condition. The objective of this study was to examine the efficacy of SSNB for the management of adhesive capsulitis. Methods: A randomised double-blind placebo-controlled trial of SSNB and standard therapy versus placebo and standard therapy was performed. In total, 54 patients were enrolled in the study. 27 patients received a glenohumeral joint (GHJ) injection and physiotherapy plus a 3-month SSNB, and 27 patients received a GHJ injection and physiotherapy plus a 3-month placebo injection. Patients were followed to resolution of their symptoms as measured by a combination of range of movement, pain scores, Shoulder Pain and Disability Index (SPADI) scores and perceived recovery scores. The primary outcome measure was time to resolution of symptoms. Results: Participants who received the SSNB reduced the duration of their symptoms of adhesive capsulitis by an average of 6 months (mean time to resolution 5.4 (95% CI 4.4 to 6.3) months vs 11.2 (95% CI 9.3 to 13) months) in the placebo group. They also had reduced pain scores, improved range of movement and lower SPADI scores compared with the placebo group across all time points. Conclusion: SSNB reduced the duration of adhesive capsulitis and resulted in improved pain and disability experience for patients. Trial registration number: Australian New Zealand Clinical Trials Registry (ANCTRN 12615001378516).